Analysis of Factors Influencing Cognitive Function Decline in Elderly Prolanis Patients with Type 2 Diabetes Mellitus in the Kedungjajang Community Health Center Working Area, Lumajang - Dewi Agustin Wulandari; Achmad Kusyairi; R. Endro Sulistyono (KHD Production, 2025)
Diabetes mellitus is a metabolic disorder characterized by persistent chronic hyperglycemia due to hormonal disturbances such as insulin resistance. Decreased cognitive function can start from the mildest form, such as being prone to forgetfulness, progress to mild cognitive impairment and eventually to dementia, the most severe clinical form. This study aims to explore the cognitive function and characteristics of elderly patient in the working area of the Kedungjajang Community Health Center. This research used a correlational analytic method with a cross-sectional approach. The study was conducted in the Kedungjajang Community Health Center Working Area. The respondents were elderly patients suffering from type 2 diabetes mellitus. Purposive sampling was utilized in this study during JuneJuly 2024. Interviews with patients were conducted using the Mini-Mental State Examination (MMSE) questionnaire. Among the 95 participants, the age group majority was 45-59 years (61.1%), with a predominant female gender distribution (83.2%). The duration of suffering from type 2 diabetes mellitus was most commonly less than 5 years (75.8%), with glucose levels over 200 mg/dl (53.7%). The analysis of this study used bivariate and subsequent multivariate tests, revealing a p-value (<0.25), indicating a significant correlation between the duration of illness and the decline in cognitive function. The results of this study are expected to educate about the importance of maintaining stable glucose levels to prevent worsening cognitive factors.